The role of peripheral innate immune cells in Alzheimer’s disease progression - Cao, Yanchun; Tang, Ke; Ma, Pengcheng; Zhang, Run; Yang, Yani; Li, Tingting; Zhang, Ying; Peng, Xiaoming (Frontiers in Immunology, 2025)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by amyloid-β (Aβ) plaques, neurofibrillary tangles, and chronic neuroinflammation. While microglia and astrocytes dominate CNS immune responses, emerging evidence implicates peripheral innate immune cells (PIICs)—including neutrophils, monocytes, dendritic cells, NK cells, and myeloid-derived suppressor cells (MDSCs)—as critical modulators of AD pathogenesis. This review synthesizes recent advances linking PIIC-related genetic polymorphisms to AD susceptibility and progression. We highlight how PIICs traffic into the brain via chemokine signaling, where they exhibit stage-specific effects: early recruitment may limit Aβ deposition via phagocytosis, whereas chronic infiltration exacerbates neuroinflammation and neuronal death. Paradoxically, some PIICs exert immunosuppressive effects that could be harnessed therapeutically. We further discuss preclinical strategies to modulate PIIC function, such as CCR2 inhibition, neutrophil depletion, and MDSC adoptive transfer. By bridging peripheral and central immunity, this review unveils PIICs as promising targets for next-generation AD therapies, advocating for precision immunomodulation tailored to disease stages.